Modern Music Performance Architectural Design - Gilang Adi Pamungkas; Fajar Ikhwan Harnomo; Kemal Affandi (Jurnal Arsitektur Archicentre, 2022)
This idea was developed out of need. Displaying Contemporary Music Unsuitable buildings, particularly in urban areas. Since five years ago, Bandung, a city with a big number of fan communities, has grown by 20 per cent. As far as acoustic quality and space limitations are concerned, the accessibility of music performance halls in Bandung does not currently offer a solution to these issues. The purpose of this plan is to upgrade the production of contemporary music execution so that it becomes a standardized assembly in the Bandung region as a whole and globally, with capable acoustic innovations, so that it can serve as a benchmark in the construction of contemporary music execution structures. To address the current issue, a presentation room with an acoustic innovation strategy that is tailored to the needs of the melody exhibition will be designed. This plan will result in the creation of an option plan for assembling a contemporary music performance that conforms to the client's specifications regarding acoustic quality and room constraints. Architecture with a dynamic idea. This concept represents a desire to create a dynamic and hospitable environment, thereby encouraging clients to develop their thinking consistently. Through advanced and basic plans, with the goal of maintaining its diversity and enjoyment. Through this concept, we are expected to provide our guests with a beautiful yet comfortable environment. In addition, the outcomes of this plan can be an input for the Joint Government of West Java, the local community, and art activists, particularly musical specialists, to have the option to collaborate on the construction of performance expressions based on their respective needs using the planned methodology and strategy.